PEMANFAATAN WHATSAPP SEBAGAI MEDIA PEMBELAJARAN AKIDAH AKHLAK MASA PANDEMI COVID-19 PADA PESERTA DIDIK MTS NURUL JADID KABUPATEN MAMUJU - Muhammad Qadri; Muhammad Saddang (El-FAKHRU, 2022)
Learning process during the COVID-19 pandemic has various obstacles in its use. One of them is the lack of facilities such as cellphones, limited internet quota, and non-existent networks. It motivated/encouraged the researcher to conduct a research regarding the use of WhatsApp as AKIDAH AKHLAK learning media for students at Mts Nurul Jadid, Mamuju Regency. This research was conducted at Madrasah stanawiyah Nurul Jadid Mamuju in October 2020. The research used descriptive qualitative research with a phenomenological type. The results of the study showed that (1) the teaching and learning process of Akidah Akhlak is carried out online using the whatsapp application. The teacher prepared the material and uploaded it into the whatsapp application, the learning process began with praying and then entered the core of learning. The closing was done by making conclusions and ended by praying. The evaluation is done by giving assignments to students in the form of worksheets that were uploaded to the WhatsApp application. (2) the online learning is done by instructing the students to study a certain material that has been given, conclude it, and do assignments through the whatsapp application. (3) the obstacles experienced in using the WhatsApp application as a learning medium are related to the availability of supporting facilities for online learning, lack of understanding of students with the material provided by the teacher, easily bored/lazy, unmonitored students’ activities, and less objective evaluation. Keywords: WhatsApp, Online Learning Media, Pandemic Covid-19, Akidah Akhlak.